Propaganda, folk beliefs, and health information insights from the cholera outbreaks in the Philippines - Acevedo, Christian George (Philippine Journal of Librarianship and Information Studies)
This brief historical paper presents the case of the cholera outbreak in the Philippines during the early 20th century. The health situation and response during this period provide valuable insights into the implications of propaganda and folk beliefs to the people's decision-making and information use and dissemination regarding their health conditions. Having a deeper understanding of the indigenous and local contexts and integrating these information into governance and policymaking are crucial in establishing health literacy campaigns, particularly at the grassroots level.